Ojcowie Kościoła a teologia moralna jako nauka teologiczna - Michał Wyrostkiewicz (Vox Patrum, 2014)
Testimonies of life and faith of the Fathers of the Church, and their teaching (letter, scriptures) impact on moral theology as a theological science. First, as “loci theologici” of contemporary theology. Omitting them would result in danger to go beyond a theology in the spirit of one, catholic and apostolic Church. Then, because the actions and writings of the Fathers of the Church are examples of exploration and argumentation for today’s theologians, also moralists. Information on the life and teachings (scriptures) are conclusive, actual and current presentation morality and the confirmation of new moral-theological views and theses. For this, however, it is necessary to use the material developed by the researchers of the Fathers of the Church (specialists in patrology). They, due to its historical and philological methods and competencies, adapt antique texts and information to the needs of contemporary theologians, also moralists.